2019
DOI: 10.1002/icd.2123
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood social responsiveness predicts the general factor of personality in early adolescence

Abstract: Positively valenced personality traits are positively correlated, forming a general factor of personality or GFP. A leading interpretation of the GFP is that it reflects social effectiveness. Accordingly, the GFP has been associated with positive social outcomes in adolescence. Yet little is known about its developmental origins. Given that the GFP is partially heritable, it was hypothesized that childhood social engagement would predict the GFP in early adolescence. Archived data from the Colorado Adoption Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…The GFP has also been replicated in studies using Japanese samples (e.g., Rushton et al, 2009). Dunkel et al (2019) found that interviewer ratings of social responsiveness in the first four years of life predicted the GFP in early adolescence. Based on such findings, one prevailing interpretation of the GFP is that it reflects social effectiveness (Van der Linden et al, 2016).…”
Section: Introductionmentioning
confidence: 77%
“…The GFP has also been replicated in studies using Japanese samples (e.g., Rushton et al, 2009). Dunkel et al (2019) found that interviewer ratings of social responsiveness in the first four years of life predicted the GFP in early adolescence. Based on such findings, one prevailing interpretation of the GFP is that it reflects social effectiveness (Van der Linden et al, 2016).…”
Section: Introductionmentioning
confidence: 77%
“…This is echoed by a recent review article integrating 31 metaanalyses across 30 different clinical populations that proposes that social cognitive dysfunction is a transdiagnostic clinical marker of psychopathology (Cotter et al, 2018). Dunkel et al (2019) examined whether it was possible to identify early developmental markers of the GFP, given that the GFP is partly heritable. To do this, the authors examined firstly whether the GFP can be predicted by childhood temperament, as assessed by sociability towards strangers from ages 1-4.…”
Section: The General Factor Of Personality and Social Effectivenessmentioning
confidence: 99%
“…On average, high-GFP individuals are relatively extraverted, open to experiences, conscientious, agreeable, and emotionally stable (Musek, 2017). The GFP model has been repeatedly tested and verified across different ages and cultural groups (Do & Minbashian, 2020;Dunkel et al, 2019Dunkel et al, , 2022Kawamoto, Kubota, et al, 2021;Kowalski et al, 2016;Musek, 2017;Pelt et al, 2020;Wu et al, 2022). In contrast to the lower-order trait models, the existence of the highest-order personality trait model (the GFP) is trying to find the core variables that influence individual behaviors (Zhu & Yan, 2015).…”
Section: Introductionmentioning
confidence: 99%